Renal cell carcinoma with inferior vena cava involvement: prognostic effect of tumor thrombus consistency on cancer specific survival - Mager, René; Daneshmand, Siamak; Evans, Christopher P.; Palou, Joan; Martínez‐Salamanca, Juan I.; Master, Viraj A.; McKiernan, James M.; Libertino, John A.; Haferkamp, Axel; Capitanio, Umberto; Carballido, Joaquín A.; Chantada, Venancio; et al. (Journal of surgical oncology, 2016)
Background Renal cell carcinoma forming a venous tumor thrombus (VTT) in the inferior vena cava (IVC) has a poor prognosis. Recent investigations have been focused on prognostic markers of survival. Thrombus consistency (TC) has been proposed to be of significant value but yet there are conflicting data. The aim of this study is to test the effect of IVC VTT consistency on cancer specific survival (CSS) in a multi-institutional cohort. Methods The records of 413 patients collected by the International Renal Cell Carcinoma-Venous Thrombus Consortium were retrospectively analyzed. All patients underwent radical nephrectomy and tumor thrombectomy. Kaplan-Meier estimate and Cox regression analyses investigated the impact of TC on CSS in addition to established clinicopathological predictors. Results VTT was solid in 225 patients and friable in 188 patients. Median CSS was 50 months in solid and 45 months in friable VTT. TC showed no significant association with metastatic spread, pT stage, perinephric fat invasion, and higher Fuhrman grade. Survival analysis and Cox regression rejected TC as prognostic marker for CSS. Conclusions In the largest cohort published so far, TC seems not to be independently associated with survival in RCC patients and should therefore not be included in risk stratification models. J. Surg. Oncol. 2016;114:764-768. © 2016 Wiley Periodicals, Inc.